The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s1516-35982005000100033
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de componentes corporais de três grupos genéticos na fases de recria e terminação

Abstract: RESUMO -Com o objetivo de avaliar a composição do ganho e as curvas de crescimento de componentes corporais, foram utilizados 36 garrotes inteiros, sendo 12 Nelore, 12 ½ Holandês x ½ Zebu e 12 ½ Caracu x ½ Zebu. Animais recria (peso médio inicial de 226 kg) e terminação (peso médio inicial de 332 kg) foram mantidos em regime de confinamento até o abate, de acordo com o peso vivo: 310 a 340 kg para os animais recria e 420 a 470 kg para os terminação. Foi fornecida a mesma dieta ad libitum a todos os animais. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
(8 reference statements)
0
2
0
6
Order By: Relevance
“…However, because crossbred dairy cattle have a greater capacity to accumulate internal fat compared with beef cattle (BACKES et al, 2010;FERNANDES et al, 2005) and because internal fat is metabolically more active than external fat, the energy expenditure for its deposition and maintenance is higher and directly influences the energy requirements for maintenance (VALADARES FILHO et al, 2006). Thus, the increase in internal fat deposition associated with increased concentrate in the cattle found by Neves (2013) with the same animals of this study may have contributed to the high NE m found compared with the data reported in the Brazilian literature.…”
Section: Resultsmentioning
confidence: 99%
“…However, because crossbred dairy cattle have a greater capacity to accumulate internal fat compared with beef cattle (BACKES et al, 2010;FERNANDES et al, 2005) and because internal fat is metabolically more active than external fat, the energy expenditure for its deposition and maintenance is higher and directly influences the energy requirements for maintenance (VALADARES FILHO et al, 2006). Thus, the increase in internal fat deposition associated with increased concentrate in the cattle found by Neves (2013) with the same animals of this study may have contributed to the high NE m found compared with the data reported in the Brazilian literature.…”
Section: Resultsmentioning
confidence: 99%
“…Por outro lado, os animais Guzolando tiveram maior participação de raça taurina (Holandês) selecionada para produção de leite. A literatura reporta maior participação de órgãos e gordura visceral no ganho de peso de corpo vazio de animais F1 Holandês x Zebu comparado a cruzamentos entre taurinos e zebuínos selecionados para corte (Fernandes et al, 2005 Rev. Bras.…”
Section: Resultsunclassified
“…Na quarta geração do cruzamento, os pesos relativos destes constituintes nos animais mestiços também foram menores que nos puros, porém a heterose foi significativa apenas para o peso relativo da cabeça. Superioridade no peso relativo da cabeça de animais mestiços (½Caracu ½Nelore) sobre animais Nelore foi citada por Fernandes et al (2005). Por outro lado, neste Tabela 4 -Pesos absolutos de cabeça, patas, vassoura da cauda, couro e do conjunto dos órgãos externos de novilhos resultantes de cruzamentos Charolês × Nelore 3,69 ± 0,2 1,88 ± 0,1b 0,06 ± 0,02 10,37 ± 1,0 15,99 ± 1,0 Média puros 3,93 ± 0,2 2,03 ± 0,1 0,09 ± 0,01 9,63 ± 0,8 15,67 ± 0,6 ¾C ¼N 3,68 ± 0,2 2,04 ± 0,1 0,08 ± 0,02 10,40 ± 1,0 16,19 ± 1,0d ¾N ¼C 3,57 ± 0,2 1,93 ± 0,1 0,08 ± 0,01 8,25 ± 0,9 13,82 ± 0,8c Média G2 3,63 ± 0,1 1,99 ± 0,1 0,08 ± 0,01 9,32 ± 0,7 15,01 ± 0,6 Heterose G2, % -7,64 -2,22 -5,88 -3,22 -4,24 5/8C 3/8N 3,26 ± 0,1 1,80 ±0,1 0,09 ± 0,01 8,54 ± 0,4 13,69 ± 0,5 5/8N 3/8C 3,37 ± 0,1 1,81 ± 0,1 0,08 ± 0,01 8,91 ± 0,4 14,17 ± 0,4 Média G3 3,32 ± 0,1 1,81 ± 0,1 0,08 ± 0,01 8,73 ± 0,3 13,93 ± 0,3 Heterose G3, % -15,54*** -11,08** 00,00 -9,44* -11,10*** 11/16 C 5/16 N 3,20 ± 0,2b 1,67 ± 0,2 0,07 ± 0,01 8,75 ± 0,5 13,69 ± 0,6 11/16 N 5/16 C 3,62 ± 0,2a 1,87 ± 0,1 0,08 ± 0,02 9,39 ± 0,5 14,97 ± 0,6 Média G4 3,41 ± 0,1 1,77 ± 0,1 0,08 ± 0,01 9,07 ± 0,4 14,33 ± 0,4 Heterose G4, % -13,12* Entre os animais puros, a única diferença que permaneceu em relação aos pesos absolutos foi o peso relativo das patas, que foi 13,76% maior (P<0,10) nos animais Charolês (Tabela 5 e 6).…”
Section: Resultsunclassified